Potensi Air Kondensat Sebagai Media Pendingin Untuk Aplikasi Modul Evaporative Cooling Terhadap Performansi AC Split 1 PK - Muhammad Rif’at Syahnan; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Air Conditioning (AC) machines with standard vapor-compression cycle has higher energy consumption, because the condenser is directly cooled by outside air. The condensate from evaporator has a temperature around 10-15°C. This study is determined the potential of evaporative cooling by using the condensate as a cooling medium for the condenser of incoming air cooler. This study used experimental method by testing of the effect of water condensate usage with the performance of standard of vapor compression cycle. The results showed that the using of Evaporative Cooling (EC) can reduce the incoming air into the condenser with an average temperature of 29.14 ° C (without cooling load) and 30.96 ° C (with 2000 W of cooling load). Then, the average working of the compressor without cooling load, before using EC was 0.60 kW and after using EC of 0.55 kW. A given cooling load of 2000 W was revealed an average working of compressor of 0.63 kW (without EC) and 0.59 kW (with EC). The compressor works decreased due to the using of an evaporative cooler.Keywords: Evaporative cooling, Condensate, Compressor work.